2021
DOI: 10.3390/ma14092213
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sintering Temperature of Kaolin, Slag, and Fly Ash Geopolymers on the Microstructure, Phase Analysis, and Electrical Conductivity

Abstract: This paper clarified the microstructural element distribution and electrical conductivity changes of kaolin, fly ash, and slag geopolymer at 900 °C. The surface microstructure analysis showed the development in surface densification within the geopolymer when in contact with sintering temperature. It was found that the electrical conductivity was majorly influenced by the existence of the crystalline phase within the geopolymer sample. The highest electrical conductivity (8.3 × 10−4 Ωm−1) was delivered by slag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The higher sintering temperature resulted in larger pores due to water removal, and the increased pore size increased the water absorption capacity of the kaolin-based geopolymer samples. The high volume of open pores in the samples may have contributed to the high water absorption due to a high surface area, which was reported by Zulkifli et al [ 11 ].…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The higher sintering temperature resulted in larger pores due to water removal, and the increased pore size increased the water absorption capacity of the kaolin-based geopolymer samples. The high volume of open pores in the samples may have contributed to the high water absorption due to a high surface area, which was reported by Zulkifli et al [ 11 ].…”
Section: Resultsmentioning
confidence: 80%
“…The NaOH clear solution was mixed with sodium silicate solution and cooled to ambient temperature one day before mixing [ 10 ]. The solid–liquid and Na 2 SiO 3 /NaOH were fixed at 1.0 (NaOH molarity 8 M) and 1.5, respectively, on the basis of previous research on the optimum design of kaolin geopolymer [ 11 ]. The kaolin materials were mixed with an alkaline activator solution for 5 min; then, the homogenized mixture was poured into a mold.…”
Section: Methodsmentioning
confidence: 99%
“…The identification of inorganic industrial by-products that can replace Portland cement, and the use of industrial by-products [18][19][20][21] to reduce pollution and the environmental burden, have become research hotspots in environmental protection. The alkali-activated gel material is a mixture of aluminosilicate and alkali metal hydroxide or alkali metal silicate solution [22,23], which is an inorganic polymer. At present, the most widely used aluminosilicate materials in alkali-activated gel materials are fly ash and metakaolin.…”
Section: Introductionmentioning
confidence: 99%
“…Wang [29] studied the effect of different silicates on the strength of alkali-activated fly ash and slag. Nur [23] studied the effect of sintering temperature on the microstructure, phase analysis, and electrical conductivity of alkali-activated materials. Guilherme Jorge Brigolini Silva [30] and others have used biomass fly ash and glass powder as precursor materials to produce alkali-activated gel materials and found that, with the increase in NaOH concentration and the decrease in glass powder content, the compressive strength and the flexural strength showed improvements, but there was still larger porosity.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of the binding time on the ion exchange and the end of the polycondensation process was demonstrated using variable frequency conductivity measurements taken in a specially designed electrode setup across a long ageing time, while geopolymers were stored in ambient conditions. Typically, concretes conductivity is measured using two-point uniaxial method or Wenner four-point probe method [ 27 , 28 , 29 ]. The second one is widely accepted but is sensitive to the surface condition.…”
Section: Introductionmentioning
confidence: 99%